Effect of early nutritional initiation on post‐cerebral infarction discharge destination: A propensity‐matched analysis using machine learning. Issue 2 (19th December 2021) - Ikezawa, Kazuto; Hirose, Mitsuaki; Maruyama, Tsunehiko; Yuji, Koichiro; Yabe, Yoshito; Kanamori, Takeshige; Kaide, Naohiro; Tsuchiya, Yusuke; Hara, Seigo; Suzuki, Hideo
Abstract: Aim: Malnutrition is associated with poor outcomes in cerebral infarction patients, with research indicating that early nutritional initiation may improve the short‐term prognosis of patients. However, evidence supported by big data is lacking. Here, to determine the effect of nutritional initiation during the first 3 days after hospital admission on home discharge rates, propensity score matching was conducted in patients with acute cerebral infarction. Methods: This retrospective observational study, using the Diagnosis Procedure Combination anonymised database in Japan, included 41 477 ischaemic cerebral infarction patients hospitalised between 2016 and 2019. The patients were divided into two groups: those who received oral or enteral nutrition during the first 3 days of hospital admission (early nutrition group, n  = 37 318) and those who did not (control group, n  = 4159). One‐to‐one pair‐matching was performed using propensity scores calculated via extreme gradient boosting to limit the confounding variables of the two groups. Results: After propensity score matching, 3541 pairs of patients were selected. The dependence of home discharge rates on early nutrition was significant ( p  < 0.05), and the effectiveness of early nutrition for home discharge showed an odds ratio of 1.79 (95% confidence interval of 1.59–2.03 in Fisher's exact test). Conclusions: Our findings revealed that early nutritional initiation during the first 3 days of admission resulted in higher home discharge rates.